ANALISIS PENDAPATAN USAHA KOPRA DI DESA MELI KECAMATAN BALAESANG KABUPATEN DONGGALA - Gafur, Abd.; Lamusa, Arifuddin (AGROTEKBIS, 2017)
Copra is a derivative product of coconut plants cultivated by the people of Indonesia. This commodityis generally used as raw material for coconut oil. Copra is produced from dried coconut meat by reducingwater contents up to 50%. One kilogram of copra is derived from four large coconuts. This study aimed to determine how much revenue received by the producers of copra in Meli Village Balaesang District Donggala Regency. This research was conducted in Meli Village Balaesang District Donggala Regency from March to May 2016 on the grounds that Meli Village Balaesang District Donggala Regency was one of copra producing regions. The number of respondents was amounted to 30 of the total 60 people who had been conducting copra processing business. Respondent determinationwas done using simple random sampling method. The primary data in this study were obtained by means of direct observations and interviews with selected respondents using questionnaires, while secondary data were obtained from related literatures and institutions. The results of this study showed that the revenue received by the producers of copra in Meli Village Balaesang District Donggala Regencywas amounted to Rp 189.143.855/three months period, with average amounted to Rp 6.304.795,00/three months period.Â Keywords : Copra, producer, revenue.